PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2013 - NUR IHTIARI WAHYUDI, SOFA (Jurnal Akuntansi AKUNESA, 2014)
Theresearchpurpose to analyze the relationship and influence of Value Added Intellectual coeficient (VAIC) on financial performance miscellaneous industry of sectors of the industry's profitability as measured by ROA and ROE. The IC analysis as a step to increase the value of the company and achieve good performance as stock competition in the industry. Of all populations in the various industry sectors acquired 13 companies already comply with the criteria that were visited during the year 2010-2013. Analysis of the data used in the test VAIC and financial performance adalaah multiple linear regression analysis. The results of this study indicate that there are significant Intellectual postitif coeficient on the company's financial performance (profitability) and significant influence. Keywords: Intellectual Capital, Value Added Intellectual Coeficient (VAIC), ROA, ROE, and Miscellaneous Industry Sector.